The Impact of Breast Clinic on the Mastectomy and Axillary Clearance Rates at a Tertiary Hospital in an Eastern Caribbean Nation: A Comparative Study - Islam, Shariful (Int J Breast Cancer, 2019)
BACKGROUND: Breast cancer is the leading form of cancer in women in Trinidad and Tobago. Traditionally the practice of mastectomy or wide local excision with or without axillary clearance was applied to most of these patients. This is often associated with significant morbidity and a poor cosmetic outcome with both negatively impacting the patients quality of life. The aim of our study was to assess the mastectomy and axillary clearance rate before and after the introduction of a specialty breast clinic in September 2012. DESIGN AND METHODS: This is a retrospective comparative study of all female patients who underwent breast cancer surgery at our tertiary hospital 3 years prior to and 3 years after starting of breast clinic (between January 2010 and December 2015). Patients were identified from the surgical log books of our hospital. There are 5 surgical units at our hospital and in one of those units the lead surgeon had a special interest in surgical oncoplastic breast surgery. That unit formed the breast clinic in August 2012. RESULTS: There were 532 women (256 before breast clinic and 276 after breast clinic era) with histologically verified breast cancer operated on between January 2010 and December 2015. The overall mastectomy rate was reduced from 62% to 51% (0.7 to 0.4) and the axillary clearance rate from 66.79% versus 37.31% (0.6 to 0.4) after the introduction of the clinic with p values of 0.007 and 0.009, respectively. CONCLUSIONS: The introduction of breast clinic has significantly reduced the mastectomy and axillary clearance rate at our teaching hospital.